Life enrichment for workers in contemporary China - Zhao, Yang; Fujimoto, Yuka *; Gaur, Sanjaya S. * (Emerald, 2018)
Purpose – The purpose of this paper is to identify key antecedents of work-family enrichment (WFE) for Chinese workers in China. The paper adopts the Chinese cultural perspectives (i.e. philosophy of Confucian: Chinese family orientation and collectivism) as well as traditional Chinese philosophies of life as a whole. Design/methodology/approach – This is a conceptual paper. Therefore, this section does not apply. Findings – The key antecedents of Chinese WFE have been identified and presented in the conceptual framework. Testable propositions have also been developed and presented in this paper. Practical implications – The conceptual framework showing the identified key antecedents of Chinese WFE highlights the necessity for the corporate leaders to rethink the ways to promote well-being and productivity of Chinese workforce in China. Meanwhile, managers should rethink about WFE among Chinese employees and regard employees as a whole person rather than just a worker with certain skills or abilities. Originality/value – This is the first paper to propose the concept of life enrichment by examining the antecedents of WFE particularly from the Chinese philosophical and cultural perspective.